Seagate Londonderry : a case study on competitiveness in a global manufacturing industry. - Siaw, Eugene. (2008)
Seagate Londonderry faced challenges represented by two cross currents, the relentless competition in the hard drive industry and the outsourcing trend. These two cross currents collectively gave rise to problems and dilemmas that the management in Londonderry needed to resolve. Londonderry's management handled these problems by focusing their strategy on their core competencies and leveraging inherent strengths to best advantage.